Estimating the global economic benefits of physically active populations over 30 years (2020-2050) - Hafner, M; Yerushalmi, E; Stepanek, M; Phillips, W; Pollard, J; Deshpande, A; Whitmore, M; Millard, F; Subel, S; van Stolk, C (BMJ Publishing Group, 2020)
Objectives We assess the potential benefits of increased physical activity for the global economy for 23 countries and the rest of the world from 2020 to 2050. The main factors taken into account in the economic assessment are excess mortality and lower productivity.